Comparative pulmonary toxicities of lunar dusts and terrestrial dusts (TiO2 & SiO2) in rats and an assessment of the impact of particle-generated oxidants on the dusts' toxicities. (21st March 2022) - Lam, Chiu-wing; Castranova, Vincent; Zeidler-Erdely, Patti C.; Renne, Roger; Hunter, Robert; McCluskey, Richard; Scully, Robert R.; Wallace, William T.; Zhang, Ye; Ryder, Valerie E.; Cooper, Bonnie; McKay, David; et al.
Abstract: Humans will set foot on the Moon again soon. The lunar dust (LD) is potentially reactive and could pose an inhalation hazard to lunar explorers. We elucidated LD toxicity and investigated the toxicological impact of particle surface reactivity (SR) using three LDs, quartz, and TiO2 . We first isolated the respirable-size-fraction of an Apollo-14 regolith and ground two coarser samples to produce fine LDs with increased SR. SR measurements of these five respirable-sized dusts, determined by their in-vitro ability to generate hydroxyl radicals (OH), showed that ground LDs > unground LD ≥ TiO2 ≥ quartz. Rats were each intratracheally instilled with 0, 1, 2.5, or 7.5 mg of a test dust. Toxicity biomarkers and histopathology were assessed up to 13 weeks after the bolus instillation. All dusts caused dose-dependent-increases in pulmonary lesions and toxicity biomarkers. The three LDs, which possessed mineral compositions/properties similar to Arizona volcanic ash, were moderately toxic. Despite a 14-fold OH difference among these three LDs, their toxicities were indistinguishable. Quartz produced the lowest OH amount but showed the greatest toxicity. Our results showed no correlation between the toxicity of mineral dusts and their ability to generate free radicals. We also showed that the amounts of oxidants per neutrophil increased with doses, time and the cytotoxicity of the dusts in the lung, which supports our postulation that dust-elicited neutrophilia is the major persistent source of oxidative stress. These results and the discussion of the crucial roles of the short-lived, continuously replenished neutrophils in dust-induced pathogenesis are presented.